Self-Concealment and Emotional Intelligence as Predictors of Seeking Psychological Help among Undergraduate Students - Demir, Ramazan; Murat, Mehmet; Bindak, Recep (Asian Journal of Education and Training, 2020)
In this study we investigate self-concealment, emotional intelligence and seeking psychological help among undergraduate students in Turkey. The attitudes toward seeking professional psychological help–short form (SPH), Self-concealment scale (SC) and Emotional Intelligence Scale (EI) were used and data were collected from a total of 785 university students studying in various faculties. As a result of the analysis, it was found that the psychological levels of the participants differed according to gender for seeking of psychological help, self-concealment and emotional intelligence. Moreover, self-concealment levels differed only according to perceived parental attitudes and the levels of seeking psychological help differed only according to whether or not they had previously received psychological help. However, the levels of seeking psychological help, self-concealment and emotional intelligence did not differ depending on whether the participants received a scholarship, were members of the community or were studying in the department of their choice. The results of Pearson’s correlation showed a positive significant relationship between seeking psychological help and emotional intelligence (r=0.124), self-concealment and emotional intelligence (r=0.118). Beside, negative significant relationship between seeking psychological help and self-concealment (r = -0.133). The results of the regression analysis showed that self-concealment, emotional intelligence, who prior receiving psychological help and gender (male) are predictive of the seeking psychological help among students and explain 8.6% of the total variation of student’s attitude toward seeking psychological help.